Recent Advances in the Functional Roles of Non‐Coding RNAs in Pancrustacea - Shumin Xie; Lihan Wang; Mengqiang Wang; Zhe Qu; Zhenmin Bao (Reviews in Aquaculture, 2026)
Non‐coding RNAs (ncRNAs), including small ncRNAs (e.g., miRNA, siRNA, piRNA), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), do not encode proteins but play crucial roles in gene regulation, growth, development, metabolism, and immune responses in metazoans. Pancrustacea is the largest clade of the phylum Arthropoda, including many important species such as shrimps, crabs, and insects. In recent years, an increasing number of ncRNAs have been identified and found to play diverse roles in a variety of biological and physiological processes of different species. Thus, this review summarizes the involvement of various ncRNAs in critical biological processes such as molting, metamorphosis, growth, reproduction, and immunity in pancrustaceans. It highlights how miRNAs regulate molting and metamorphosis through pathways involving ecdysteroids and sesquiterpenoid hormones, and discusses the regulatory functions of lncRNAs in muscle growth, wing development, and sexual differentiation. Moreover, the involvement of ncRNAs in immune responses against viral and bacterial infections is also reviewed, revealing their potential to improve pathogen resistance. These insights into ncRNA‐mediated gene regulation in pancrustaceans provide a foundation for future research and applications in aquaculture and breeding improvement, disease prevention and control, and ecological conservation.